ENTEROCOCCUS: AN EMERGING PATHOGEN - Arelis Lleras de Torres (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2000)
The importance of Enterococcus spp has been increasing gradually, nowadays it is considered one of the most important nosocomial pathogens, it is responsible of 12% of al1 hospital acquired infections and 5-10% of bacferemias.The appearance of multiple antimicrobial resistance has produced therapeutic controversy. The application of control measures for appropiate use of antibiotics is necessary, specially for extended spectrum cephalosporins and vancomycin in order to decrease the emergence of multiresistant Enterococcus spp.